(untitled) (Al-Academy, 2020)
The current research is interested in studying the symbol, due to its significant role in the architecture and arts in the holy shrines regardless of their architecture and artistic patterns, through which the symbolic and philosophical connotations insides the holy shrines are revealed. Due to the importance of the topic of the symbol, Almighty God remarked in the holy Quran (He said, "My Lord, make for me a sign." He Said, "Your sign is that you will not [be able to] speak to the people for three days except by gesture. And remember your Lord much and exalt [Him with praise] in the evening and the morning.") (Surat Al-Imran, verse 41). The research consists of two dimensions dealing with symbol and symbolism in its linguistic and terminological sides. Then it addresses its historical aspect as far as its evolution and the scientists’ opinions are concerned. Then it addresses the topic of symbol and the symbolic school in arts in general and the Islamic arts in specific heading to the way of employing the symbol in the arts and architecture of the holy shrines, adopting the descriptive analytical approach in conducting this research, knowing that the spatial limits would be the Alawyyad, Hussaini, and Abbasi shrines in Iraq and the Radhawi shrine in Iran. As for the temporal limit, the researcher will tackle multiple periods that add to the research and its methodology a feature of scientific realism.